2011
DOI: 10.1073/pnas.1019644108
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila histone H2A variant (H2Av) controls poly(ADP-ribose) polymerase 1 (PARP1) activation in chromatin

Abstract: According to the histone code hypothesis, histone variants and modified histones provide binding sites for proteins that change the chromatin state to either active or repressed. Here, we identify histone variants that regulate the targeting and enzymatic activity of poly(ADP-ribose) polymerase 1 (PARP1), a chromatin regulator in higher eukaryotes. We demonstrate that PARP1 is targeted to chromatin by association with the histone H2A variant (H2Av)-the Drosophila homolog of the mammalian histone H2A variants H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 44 publications
2
90
1
Order By: Relevance
“…Importantly, the S139 phosphorylation of H2AX in mammalian cells is not required for the dynamics of either H2AX or PARP-1 (9 and this study). Although this contradicts the results obtained from the study in a fly system, where the phosphorylation of the H2A variant (H2Av) controlled PARP-1 upon transcriptional activation, the discrepancy may be due to differences in the biological functions of the H2A variants in the different organisms (33).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Importantly, the S139 phosphorylation of H2AX in mammalian cells is not required for the dynamics of either H2AX or PARP-1 (9 and this study). Although this contradicts the results obtained from the study in a fly system, where the phosphorylation of the H2A variant (H2Av) controlled PARP-1 upon transcriptional activation, the discrepancy may be due to differences in the biological functions of the H2A variants in the different organisms (33).…”
Section: Discussioncontrasting
confidence: 74%
“…To facilitate the recruitment of transcription factors, the chromatin must be remodeled. Chromatin decondensation or histone exchange at transcription sites occurs in response to extracellular stress such as heat shock, and the activation of PARP-1 promotes this process (33,42,43). PARP-1 activation at transcription sites is likely to require nucleosomes, as they can accommodate PARP-1 (44).…”
Section: Discussionmentioning
confidence: 99%
“…2C). His2Av 810 is a null allele that contains a 311 bp deletion that removes the region surrounding and including the second exon of the gene (van Daal and Elgin, 1992 (Kotova et al, 2011). In order to test whether the formation of the melanotic masses was due to the loss of H2AV, rather than some other unknown mutation in the genetic background of the homozygous animals, we crossed His2Av 810 /+ heterozygotes with flies heterozygous for Df(3R)BSC524, a large deletion mutant with molecularly defined endpoints in the same region of the genome (Cook et al, 2012).…”
Section: Loss Of H2av Causes Melanotic Masses In Drosophila Larvaementioning
confidence: 99%
“…Histone proteins are highly vulnerable to post-translational modification at specific amino acids. The covalent post-translational modifications include but are not limited to methylation (13), acetylation (14), phosphorylation (15), ubiquitination (16), sumoylation (17), biotinylation (18), and ADP-ribosylation (19). To date, only one study has recently demonstrated by mass screening histone S-palmitoylation; however, the identity of the acyltransferase that catalyzes this reaction was not investigated (20).…”
mentioning
confidence: 99%